Effects of Model-Specific Parameters on the Development of Custom Module in PX4 Autopilot Software-in-the-Loop - Abera Tullu; Sunghun Jung; Sangchul Lee; Sangho Ko (International Journal of Aerospace Engineering)
Software-in-the-loop simulation tools have been extensively used in the development of safety-critical software. Utilizing these tools substantially accelerates software development, eliminating potential risks and resource costs of physical experiments. This paper investigates the effects of model-specific parameters on the development and testing of custom modules in a simulation environment. Models of a fixed-wing unmanned aerial vehicle with vertical takeoff and landing capabilities and a steerable sensor platform/gimbal are used as a case study for this investigation. The effects of parameters of these aerial vehicle and sensor platform models are taken into consideration in the development of a custom module that is incorporated into PX4 Autopilot and controls the dynamics of the steerable sensor platform mounted on the vehicle model. The work also presents steps necessary to customize the PX4 Autopilot software-in-the-loop tool and Gazebo simulation environment to incorporate parameters of the vehicle and sensor platform models in the development and testing process of the custom module. Based on these instances, simulation results are obtained and discussed. The results show that the effective use of the PX4 Autopilot software-in-the-loop simulation framework is justified by its proper customization and integration with the Gazebo simulator.